Методи та засоби безконфліктного обміну даними у групі мобільних робототехнічних платформ - Цмоць, І. Г.; Опотяк, Ю. В.; Обельовська, К. М.; Теслюк, С. В.; Tsmots, I. G.; Opotiak, Yu. V.; Obelovska, K. M.; Tesliuk, S. V. (Видавництво Львівської політехніки, 2024)
Під час використання груп мобільних робототехнічних платформ (МРП) виникають проблеми, пов’язані із керуванням окремими платформами, організацією співпраці в групі та забезпеченням управління групою загалом. Управління групою МРП передбачає керування діями окремих платформ для досягнення загальної мети групи. Для забезпечення управління групою МРП у такому випадку доцільно вибрати гібридний метод, що вимагає вирішення проблеми безконфліктного обміну даними та командами керування між МРП у групі. Для вирішення вказаної проблеми запропоновано удосконалити відповідні методи та засоби. Гібридний метод управління враховує переваги централізованого і розподіленого залежно від конкретних завдань та умов використання. Запропоновано для обміну даними за гібридного управління використовувати багатоканальний пристрій безконфліктного обміну із використанням методу часового розподілу ресурсів ОЗП. Показано, що глобальні мережі із низьким енергоспоживанням LPWANs (Low-Power Wide Area Networks) можна використовувати для передавання невеликих блоків даних із низькою швидкістю, організовуючи обмін із МРП. Запропоновано для передавання трафіку, некритичного до часу, застосовувати слотовий механізм СSMA/CA, а для критичного до часу – керований координатором доступ із використанням гарантованих часових слотів. Показано, що ефективність роботи мережі упродовж безконфліктного періоду доступу залежить від результатів розподілу гарантованих часових слотів між активними користувачами. Вибрано технологію LoRa для обміну даними на великих відстанях між МРП, яка на рівні управління доступом до фізичного середовища МАС дає змогу планувати передавання та управляти зв’язком між кінцевими пристроями та шлюзами, уникаючи зіткнень та оптимізуючи продуктивність мережі.

When using groups of mobile robotic platforms (MRP), problems arise related to the management of individual platforms, the organization of cooperation in the group, and the management of the group as a whole. Management of the MRP group involves managing the actions of individual platforms to achieve the group's overall goal. To ensure the management of the MRP group in such a case, it is advisable to choose a hybrid method that requires solving the problem of conflict-free data exchange and control commands between the MRPs in the group. To solve this problem, it is proposed to improve the relevant methods and tools. The scientific novelty of the obtained research results is that a method of multi-channel conflict-free data exchange has been developed, which provides a real-time mode due to the coordination of the intensity of data arrival with the intensity of access. The method of controlling the movement of a group of mobile robotic platforms has been improved, which, by taking into account the changing parameters of the platforms and the changing state of the surrounding environment, provides effective management of the MRP group in real time. The practical significance of the research results is that it is proposed to use the CSMA/CA slotted mechanism for non-time-critical traffic to improve performance, and for time-critical traffic, coordinator-controlled access using guaranteed time slots. The hybrid method of management takes into account the advantages of centralized and distributed depending on specific tasks and conditions of use. It is proposed to use a multi-channel device for conflict-free exchange using the method of time allocation of RAM resources for data exchange in hybrid control. It is shown that global low-power networks LPWANs (Low-Power Wide Area Networks) can be used to transmit small blocks of data at a low speed when exchanging with MRP. It is proposed to use the slotted CSMA/CA mechanism for the transmission of non-time-critical traffic, and for time-critical traffic, coordinator-controlled access using guaranteed time slots. It is shown that the performance of the network during the conflict-free access period CFP depends on the results of the distribution of guaranteed GTS time slots among active users. LoRa technology was selected for long-distance data exchange between MRPs, which at the MAC (Media Access Control) sublayer allows for transmission planning and communication management between end devices and gateways, avoiding collisions and optimizing network performance.
Methods and means of conflict-free data exchange in the group of mobile robotic platforms
Keywords: управління мобільними робототехнічними платформами; передавання даних; управління доступом до середовища передачі; безконфліктний доступ; management of mobile robotic platforms; data transmission; media access control; conflict-free access; 004.94